VEKALET TEORİSİ VE KAYNAK BAĞIMLILIĞI TEORİSİ BAĞLAMINDA, YÖNETİM KURULUNUN YAPISAL ÖZELLİKLERİ İLE FİNANSAL KALDIRAÇ VE KARLILIK ORANLARI ARASINDAKİ İLİŞKİ: HALKA AÇIK GIDA ŞİRKETLERİ ÜZERİNDE BİR ARAŞTIRMA (2005-2016 DÖNEMİ) - (:unkn) unknown (My University, 2018)
Çalışmada, vekalet teorisi ve kaynak bağımlılığı teorisi çerçevesinde, bir kurumsal yönetim mekanizması olarak yönetim kurulunun yapısal özellikleri ve yönetim kurullarının rolleri ile finansal performans arasındaki ilişkinin araştırılması amaçlanmıştır. Bu amaçla, halka açık gıda şirketlerinde çalışan on bir üst düzey yönetici ile yapılan görüşmelerden elde edilen veriler NVivo 8 nitel veri analizi programı kullanılarak analiz edilmiştir. Elde edilen sonuçlar, örneklemde yer alan şirketlerin çoğunluğunun aile şirketi olduğunu, buralarda ayrıntılı denetim süreçleri sayesinde minimum düzeyde vekalet problemi yaşandığını, dolayısıyla vekalet maliyetlerinin maksimum düzeyde olduğunu ortaya koymaktadır. Ayrıca, kritik kaynak olarak hammadde ve finansal kaynaklar üzerinde durulduğu, bağımlılığın daha çok yasal düzenlemeler açısından devlete karşı olduğu ve yönetim kurulu üyelerinin seçiminde en çok pay sahibi olmanın etkili olduğu görülmüştür. Yönetim kurulunun yapısal özelliklerinin finansal performans ile ilişkisi değerlendirildiğinde, halka açık gıda şirketlerinde bu özelliklerin tek başına finansal performans ile ilişkisi olabileceğini gösteren bir bulguya rastlanmamıştır. Örneklemde yer alan şirketlerin zarar ediyor olmalarında, analize konu olan on yılda (2006-2015) dünyada ve Türkiye’de yaşanan ekonomik ve siyasi krizlerin etkileri de göz önünde bulundurulmalıdır.

This study aims to investigate relationship between the structural characteristics of board of management (the size of board of management, the number of independent members, business variety of board of management) and the role of board of management (monitoring role, resource supplier role, service role) with financial performance (financial leverage ratio, return on assets, return on sales) within the scope of the agency theory and resource dependence theory, as a corporate governance mechanism. Research in the field of corporate governance has been made in contexts where companies with dispersed ownership dominate such as the United States and the United Kingdom. Publicly traded companies in Turkey have intensive ownership structures. The regulations relating to board structure in the area of corporate governance is not yet fully implemented in Turkey. The fact that the number of family companies is high is a disadvantage in this sense. The results of this study are valuable in terms of showing the current situation in Turkey. The data of this study obtained from meeting with eleven senior managers working in the publicly traded food companies, is analyzed with NVivo8 qualitative data analysis program. Investigation results show that most of the companies taking part in the sample are family companies. Managers have indicated that there is no agency problem in their company and in order not to have agency problem they take many supervision precautions so that the most important monitoring cost is agency cost in their companies. It is seen that critical resources are raw materials and financial resources. It should be indicated that the type of the raw material differentiates according to the sub-sector of the company. When the views about dependency are interpreted it has been determined that firstly, companies are dependent to the government because of legal reforms and secondly they feel dependent to the raw material suppliers. However, the number of companies that feel dependent to the raw material suppliers are three. The most important reason of this is companies’ having been working with many suppliers. The average size of the board of management of the companies taking part in the sample is seven. So, they are in ideal board of management size. It is seen that in selection of board of management, the first important thing is having the largest share in company and then having experience. The reason of this measure is that most of publicly traded food companies are family companies. It is determined that board of managements that have mostly family members have mainly monitoring roles. It has seen that the average independent board member number of the companies taking part in the sample is two and these members have mainly resource supplier roles. When the occupations of the board members are spotted, it is seen that the members are from different occupations such as director, academic, financier, accountant, engineer, policeman, journalist. As they have different occupational backgrounds, it is anticipated that they give different point of views to the company. On the other hand, as each of them has different networks out of the company because of their occupations, they help the company to get in touch with these organizations. When the relationship between the structural characteristics of board of management and financial performance is consider, no evidence was found to reveal that these features have a relationship with financial performance by itself in the publicly traded food companies. The companies in the sample are making losses, the effects of economic and political crisis in Turkey and the worldwide among ten years (2006-2015) should be taken into consideration. The mortgage crisis that emerged in the US in 2007 increased the current deficit as a result of the increase in the exchange rate. This situation affected all companies operating in the real sector, including the food sector in Turkey. Tensions between Turkey and Russia in 2014 were also negatively affect the food industry by reducing the export of food to Russia. Otherwise, there is need for the new researches that will analyze the companies in terms of financial data which include before 2006. Arranging the structure of the board of directors of publicly traded companies as pointed out by the theory of agency and the theory of resource dependence will be both a factor in increasing institutionalization and financial performance. Therefore, the potential benefits of universally accepted corporate governance regulations should be evaluated in a comprehensively by the company and these arrangements should be made functional in particular Turkey. While doing this, in Turkey, economic, legal, moral and managerial characteristics should be considered.
THE RELATIONSHIP BETWEEN THE STRUCTURAL CHARACTERISTICS OF THE BOARD AND FINANCIAL LEVERAGE AND PROFITABILITY RATIOS IN THE CONTEXT OF AGENCY THEORY AND RESOURCE DEPENDENCE THEORY: A RESEARCH ON PUBLICLY TRADED FOOD COMPANIES (2005 - 2016 PERIOD)